Curiosity and Critical Thinking: Identifying Child Abuse Before It Is Too Late. (January 2015) - Jackson, Allison M.; Deye, Katherine P.; Halley, Tina; Hinds, Tanya; Rosenthal, Eric; Shalaby-Rana, Eglal; Goldman, Ellen F.
Objective . We reviewed medical records to identify factors contributing to not recognizing child abuse in cases where it was subsequently identified. Design/Methods . Eighteen cases of delayed diagnosis of physical abuse were reviewed for qualitative themes. Missed abuse was defined by prior medical encounters that revealed findings concerning for physical abuse that were not recognized. Results . Clinical limitations contributing to a delay in diagnosis included inattention to skin and subconjunctival findings, acceptance of inadequate explanations for injuries, no history obtained from verbal children, insufficient exploration of signs and symptoms, nonadherence to the maltreatment pathway, and incorrect diagnoses from radiologic examinations. System-based limitations included limited medical record access or completeness and admission to less-than-optimal settings. Conclusions . Having a greater index of suspicion for abuse may mitigate missed opportunities. With variability of medical training in child abuse, the factors we identified can be used as learning objectives for continuing medical education.